A study of variations in brachial artery and its branching pattern - Shivanal, Uma; Gowda, M. S. Trinesh (International Journal of Research in Medical Sciences, 2017)
Background: Knowledge of the normal and variant arterial anatomy of the upper extremity is of significant clinical importance for the vascular radiologist and surgeons for accurate diagnostic interpretation as well as in the conduct of interventional and surgical procedures on the upper extremity. The anatomical knowledge of the anomalous branching pattern of the brachial artery is important during percutaneous arterial catheterization, so as to prevent any complications arising from accidental damage to the anomalous vessel and knowledge of the variations are important for plastic surgeons using flaps for reconstructive surgeries. Methods: The present study was undertaken on 50 upper limbs of both sexes from embalmed adult human cadaver used for undergraduate dissection from the department of Anatomy, Mandya Institute of Medical Sciences, Mandya. Results: In the present study, normal brachial artery was found in 42 specimens accounting for 84%. Variations were found in 8 specimens (16%); of these five specimens presented with trifurcation of brachial artery into radial, ulnar and radial recurrent arteries (10%); one specimen presented with double profunda brachii artery (2%); one specimen showed high origin of radial artery (2%) and one specimen presented with high division of brachial artery in the proximal third of arm (2%). Conclusions: Accurate anatomical knowledge about the brachial artery and its branching pattern with their variations are important for physicians, cardiologists, vascular surgeons and interventional radiologists. Study of these variations and its awareness helps in avoiding the iatrogenic injuries of the blood vessels, in the management of accidental/traumatic injuries to arteries in upper limb and during diagnostic procedures (like arteriograms).